Creating “flipping-the-classroom” cases in training in sense-making and decision-making in marketing: A Journal of Global Scholars of Marketing Science Special Issue - Woodside, Arch (Taylor & Francis, 2016)
Though no one definition fully captures the proposal, “flipping-the-classroom” includes student/trainee creation of learning materials, “lesson plans”, and in-classroom administration, and/or coaching to fellow students/trainees of concepts, principles, procedures, tools, and interpretations of outcomes. This JGSMS special issue presents 11 flipping-the-classroom case studies. Most of these cases are creative writings by students. The cases include emic reports on interactions with service providers. Assigning and reading the cases may be useful for learning how to increase student joy-in-learning and deepening their skills in sensemaking and solving problems in customer–marketer interactions.